Risk for Cardiovascular Adverse Events Associated With Sphingosine-1-Phosphate Receptor Modulators in Patients With Multiple Sclerosis: Insights From a Pooled Analysis of 15 Randomised Controlled Trials - Zhao, Zhao; Lv, Yang; Gu, Zhi-Chun; Ma, Chun-Lai; Zhong, Ming-Kang (Frontiers in Immunology, 2021)
Background All agents engaging sphongosine-1-phospate receptors (S1PRs) will have some cardiovascular effect. This study aimed to elucidate the risk of cardiovascular adverse events (AEs) in patients with multiple sclerosis (MS) treated with S1PR modulators (S1PRMs). Methods We systematically searched the PubMed, EMBASE, and Cochrane Library databases for randomised controlled trials (RCTs) published through January 5, 2021. Relative risks (RRs) and 95% confidence intervals (CIs) were calculated using the random-effects model. Sensitivity analyses and meta-regression were performed. Results Seventeen RCTs (12 for fingolimod; 3 for ozanimod; 2 for siponimod) involving 13,295 patients were included. Compared with the control treatment, S1PRMs significantly increased the risk of cardiovascular AEs (RR, 2.21; 95% CI, 1.58–3.10; I2, 75.6%). Notably, the high-risk cardiovascular AEs associated with S1PRMs were primarily bradyarrhythmia (RR, 2.92; 95% CI, 1.91–4.46; I2, 30.8%) and hypertension (RR, 2.00; 95% CI, 1.49–2.67; I2, 56.5%). Subgroup analysis results were consistent with the primary outcomes except that ozanimod was associated with a higher risk of hypertension only (RR, 1.76; 95% CI, 1.10–2.82; I2, 0.0%), while siponimod was associated with a higher risk of bradyarrhythmia only (RR, 2.75; 95% CI, 1.75–4.31; I2, 0.0%). No significant inter-subgroup differences were observed (Pinteraction > 0.05). Conclusions S1PRM use increased the risk of cardiovascular AEs by 1.21 times in patients with MS, and increased risks for bradyarrhythmia and hypertension were at 2.92- and 2.00-fold, respectively. These findings can help clinicians assess the risk of cardiovascular AEs in patients treated with S1PRMs. Systematic Review Registration The PROSPERO ID is CRD42020183215.